Twisting transition between crystalline and fibrillar phases of aggregated peptides. - Knowles, T; De Simone, A; Fitzpatrick, A; Baldwin, A; Meehan, S; Rajah, L; Vendruscolo, M; Welland, M; Dobson, C; Terentjev, E (2012)
We study two distinctly ordered condensed phases of polypeptide molecules, amyloid fibrils and amyloidlike microcrystals, and the first-order twisting phase transition between these two states. We derive a single free-energy form which connects both phases. Our model identifies relevant degrees of freedom for describing the collective behavior of supramolecular polypeptide structures, reproduces accurately the results from molecular dynamics simulations as well as from experiments, and sheds light on the uniform nature of the dimensions of different peptide fibrils.